Whole-Exome Sequencing Identified CFTR Variants in Two Consanguineous Families in China - Yang, Binyi; Lei, Cheng; Yang, Danhui; Tan, Zhiping; Guo, Ting; Luo, Hong (Frontiers in Genetics, 2021)
Abstract: Background: Cystic fibrosis (CF) is an autosomal recessive disease caused by genetic variants of the cystic fibrosis transmembrane conductance regulator (CFTR) gene. It is a common hereditary disease in Caucasians while rare in Chinese. Till now, only 87 Chinese patients have been reported with molecular confirmations. The variant spectrum and clinical features of Chinese CF patients are obviously different from Caucasian. Method: Whole-exome sequencing was applied to analyze the exome of 3 individuals who only have typical CF phenotype in the respiratory system from 2 consanguineous families. Protein domain and structure analysis were applied to predict the impact of the variants. Sanger sequencing was applied to validate the candidate variants. Results: A previously reported homozygous variant in CFTR (NM_000492.4: c.1000C>T, p.R334W) was identified in proband Ⅰ. A novel homozygous variant in a polymorphic position (NM_000492.4: c.1409T>A, p.V470E) was identified in 2 individuals in the family Ⅱ. The novel CFTR variant predicted to be disease-causing is the first, to the best of our knowledge, to be reported in CFTR. However, in vitro validation is still needed. Conclusion: Our finding expands the variant spectrum of CFTR, reveals a clearer distinction of clinical phenotype and the variant spectrum between Chinese and Caucasian CF patients, and contributes to a more rapid genetic diagnosis and future genetic counseling.